Innovatisation of transport and logistics services as one of the key goals of Industry 5.0 - Baryshnikova Vira; Kovtsur Kateryna; Shapoval Ganna; Kurudzhi Yulia; Miedviedieva Natalia; Popova Yuliia (E3S Web of Conferences)
The importance of Industry 5.0 at the present stage of development is highlighted. The methodological basis of the study is represented by the methods of generalisation and system analysis, expert assessments, analysis and synthesis, graphical method, and method of analogy. The scientific novelty of the study is determined by determining the role and place of Industry 5.0 for transport and logistics market players in the context of transformational changes in the economy, as well as the creation of effective tools to increase the level of innovative development of transport and logistics services as one of the key goals within the framework of the Industry 5.0 development stage. Clarification and description of Industry 5.0 features by innovation aspects for transport and logistics service providers was carried out. An appropriate interpretation of the key steps in implementing Industry 5.0 in terms of the transport and logistics services innovatisation aspect is made. A breakthrough element for the implementation of Industry 5.0 in the aspect of innovating transport and logistics services for countries in transition and lagging far behind the leaders should be the added value chain.